The Management of Shunt Dysfunction Caused by Stent Deviation During Transjugular Intrahepatic Portosystemic Shunt (TIPS) Surgery for Esophageal and Gastric Varices Bleeding - Chen, Jin-Mao; Li, Xiang-Long; Zhang, Guo-Jie; Shen, Ning; Wei, Yu-Dong; Chen, Feng; Cui, Yan-Yan (Turkish Journal of Gastroenterology, 2024)
Cite this article as: Chen J-M, Li X-L, Zhang G-J, et al. The management of shunt dysfunction caused by stent deviation during transjugular intrahepatic portosystemic shunt (TIPS) surgery for esophageal and gastric varices bleeding. Turk J Gastroenterol. 2024;35(11):872-875.